The determination of phenazone in blood plasma for obtained sistem suitable test of monitoring drug level - Mochamad Lazuardi (Dental Journal (Majalah Kedokteran Gigi), 2007)
The determining of Phenazone to human blood plasma from healthy man after separated by solid phase extraction (SPE) and spectroscopic measurements has been investigated. The objective of that research was to obtain system suitable test for determine the Phenazone level in biological fluids (human blood plasma), for new performed dosage regimented in clinical dentistry. The method can be divided into the following four steps. 1. Centrifugation the blood sample, 2. Extraction from blood plasma and, 3. Separation by SPE with manual pressured, 4. Elution to SPE followed by the measurement on a spectrophotometer in the ultra violet region. The critical value of  │t │at the 5% confidence level indicates that there is no systematic error in the linearity proposed method. Recoveries for this research were obtained at ranging 93.460 to 95.598%. The coefficient variation precision of this procedure was clearly good at smallest than 2%. The analytical procedure can be carried out in one working operation as a monitored therapeutic activity.